Farm - Sirett, Dawn.; Harvey, Victoria; Quasha, Jennifer (London : DK Pub., 2008)
From soft piglets to woolly sheep, there are all sorts of textures for baby to explore.
Cover title: Baby touch and feel farm.
Cover title.
On board pages.
Keywords: Animals -- Juvenile literature; Domestic animals -- Infancy -- Juvenile literature; Textured books -- Specimens; Toy and movable books -- Specimens; Vocabulary -- Juvenile literature